PENERAPAN METODE BERCERITA BONEKA TANGAN UNTUK MENINGKATKAN KREATIVITAS, PENGUASAAN KOSAKATA MANDARIN, DAN KETERLIBATAN DI DALAM KELAS PADA PESERTA DIDIK TK B DI SEKOLAH MAITREYAWIRA JAKARTA [THE IMPLEMENTATION OF HAND PUPPETS AND ONLINE STORYTELLING METHODS IN INCREASING CREATIVITY, MANDARIN VOCABULARY MASTERY, AND ENGAGEMENT OF TK-B STUDENTS AT MAITREYAWIRA SCHOOL JAKARTA] - Shanti Paramita; Rudy Pramono (Universitas Pelita Harapan, 2022)
Creativity, mastery of Mandarin vocabulary, and engagement in the classroom are very important from early age to support students’ ability to mastering Mandarin. The purpose of this research is to apply online storytelling methods to improve the abilities of students aged 5-6 years in creativity, mastery of Mandarin vocabulary, and engagement in the classroom. This study used a Classroom Action Research method with preliminary research and three cycles with three meetings for each as a form of corrective action. The subjects of this study were children aged 5-6 years at Maitreyawira School Jakarta. Data collection used data triangulation, assessment rubrics, field notes, and performance results also the assessment was carried out by three observers, which are the researcher and two observers. The results showed that (1) online storytelling methods by providing opportunities to respond the events and critical thinking can increase students’ creativity, (2) online storytelling methods by listening and practicing role-play conversation activity can improve the mastery of Mandarin vocabulary, and (3) online storytelling methods with educator interaction and students can increase students’ engagements in the classroom. For the conclusion, there is an increase in the level of creativity, mastery of Mandarin vocabulary, and engagement in the class of TK B students at Maitreyawira School Jakarta. Suggestions for further research are to pay more attention to children's developments and provide more varied activitiesBahasa Indonesia Abstrak: Kreativitas, penguasaan kosakata Mandarin, dan keterlibatan di dalam kelas dibutuhkan sejak usia dini untuk menunjang kemampuan peserta didik dalam menguasai Bahasa Mandarin. Tujuan dari penelitian dalam kegiatan pembelajaran Bahasa Mandarin adalah menerapkan metode bercerita daring untuk meningkatkan kemampuan peserta didik usia 5-6 tahun dalam kreativitas, penguasaan kosakata Mandarin, dan keterlibatan di dalam kelas. Penelitian ini menggunakan metode Penelitian Tindakan Kelas dengan penelitian pendahuluan dan tiga siklus dengan masing-masing tiga pertemuan sebagai bentuk tindakan perbaikan. Subjek penelitian ini adalah anak usia 5-6 tahun di Sekolah Maitreyawira Jakarta. Pengumpulan data menggunakan triangulasi data yaitu rubrik penilaian, catatan lapangan, dan hasil unjuk kerja serta penilaian dilakukan oleh tiga pengamat yaitu peneliti dan dua pengamat. Hasil penelitian didapatkan bahwa (1) metode bercerita daring dengan memberikan kesempatan menanggapi kejadian dan berpikir kritis dapat meningkatkan kreativitas peserta didik, (2) metode bercerita daring dengan mendengarkan dan berlatih percakapan dapat meningkatkan penguasaan kosakata Mandarin, (3) metode bercerita daring dengan interaksi pendidik dan peserta didik dapat meningkatkan keterlibatan di dalam kelas. Kesimpulan dari penelitian ini adalah terdapat peningkatan pada tingkat kreativitas, penguasaan kosakata Mandarin, dan keterlibatan di dalam kelas peserta didik TK B di Sekolah Maitreyawira Jakarta. Saran untuk penelitian selanjutnya adalah lebih memperhatikan kemampuan anak dan memilih kegiatan yang lebih bervariasi.